Mentoring as More Than "Cheerleading": Looking at Educative Mentoring Practices Through Mentors' Eyes. (November 2019) - Stanulis, Randi N.; Wexler, Lindsay J.; Pylman, Stacey; Guenther, Amy; Farver, Scott; Ward, Amy; Croel-Perrien, Amy; White, Kristen
Traditionally, classroom teachers have been asked to "cooperate" during student teaching, providing advice to imitate and emotional support to meet immediate needs. Based on theories of educative experience, educative mentoring focuses on growth, continuity, and inquiry. The purpose of this study was to understand what educative practices look like through the eyes of 10 mentor teachers who participated in six mentor study groups across a school year. We report on mentor's talk about and enactment of three practices: coplanning, observing and debriefing, and analyzing student work. Although we introduced and gave name to particular mentoring practices, the mentors' interpretations of what these look like when done in educative ways helped us craft the definitions we present in our findings. The findings of this study highlight that mentors benefit from professional learning that is focused on concrete practices with opportunities to develop over time in educative ways.